HEAVY METAL CONDITION IN KRAMAT KEBO ESTUARY, WEST JAVA, INDONESIA as HABITAT of Oryzias Javanicus - Rachma Puspitasari; Lestari Lestari (Pusat Riset Kelautan, 2018)
Nowadays, contamination monitoring in Indonesia still focused on traditional method like only depend on measurement of chemical and physical parameter. In addition, the use of organism, known as bioindicator brings some advantages such as knowing about habitat alteration and relationship between organism and environment. Fish from genus Oryzias had been known in Malaysia and Japan as a sensitive bioindicator. One of species, O. javanicus, was found in Kramat Kebo estuary, West Java, Indonesia. This preliminary study aims to determine metal distribution in water and sediment in Kramat kebo estuary, as a habitat of O. javanicus. It is also a preliminary study to assess possibility of O. javanicus as a bioindicator of heavy metal contamination in coastal area. Sampling was conducted on March and September, 2014 and analysis of total metal was done by Atomic Absorbance Spectrophotometry. Result showed that metal in water still below the threshold value by Ministry of Environment. Metal in sediment analyzed by Sediment Quality Guidelines Quetiont (SQG-Q) index, showed that all stations has SQG-Q value < 0.1, which is means that Kramat Kebo estuary is unimpacted area. We conclude for this preliminary study that existence of O. javanicus were related to less polluted of heavy metal in estuary and it suitable for bioindicator of uncontaminated heavy metal area.